Systematic meta-analysis of individual selective serotonin reuptake inhibitor medications and congenital malformations. (November 2013) - Myles, Nicholas; Newall, Hannah; Ward, Harvey; Large, Matthew
Context: It has been suggested that the commonly prescribed class of antidepressants selective serotonin reuptake inhibitors (SSRIs) are associated with birth defects. However, the teratogenic effect of individual SSRIs has not been previously compared using meta-analysis. Objective: To determine the strength of the association between individual SSRIs and major, minor, and cardiac malformation among infants born to women taking these medications. Data sources: Electronic search of CINAHL, EMBASE, Medline, PsycINFO, and ISI Web of Science using the search terms (SSRI OR antidepressant) AND (obstetric outcome OR malformation OR birth outcome OR teratogen), supplemented by manual searching of published references and requests of primary researchers for unpublished data. Study selection: There were 115 studies identified by electronic search and reviewed in full text, which yielded 16 papers reporting 36 data samples for major malformations, nine papers reporting 26 data samples for cardiac malformations, and four papers reporting seven data samples for minor malformations. Data synthesis: Fluoxetine (OR 1.14, 95% CI 1.01–1.30) and paroxetine (OR 1.29, 95% CI 1.11–1.49) were associated with increased risk of major malformations. Paroxetine was associated with increased risk of cardiac malformations (OR 1.44, 95% CI 1.12–1.86). Sertraline and citalopram were not significantly associated with congenital malformation. Between-sample heterogeneity was low and a range of methodological considerations had no significant impact on effect size. There was little evidence of publication bias. Conclusions: Fluoxetine and paroxetine should be avoided in the first trimester and among those at risk of an unplanned pregnancy.